2015
DOI: 10.1155/2015/932474
|View full text |Cite
|
Sign up to set email alerts
|

Drought and Grain Crop Yields over the East European Plain under Influence of Quasibiennial Oscillation of Global Atmospheric Processes

Abstract: Monthly precipitation and the 3-month Standardized Precipitation Index (SPI) were used to reveal the patterns of rainfall and severe drought frequency over the East European Plain in the period 1953–2011 in the opposite phases of the quasibiennial oscillation (QBO). Differences of precipitation and severe drought frequency in May and in June in the westward and eastward phases of the QBO phases are explained by circulation variations. The analysis indicates less frequent severe drought events over Ukraine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
3
0
3
Order By: Relevance
“…In the southern part of the East European plain, Cherenkova et al [43] demonstrated the average yield for winter wheat, spring wheat, and spring barley in the westerly phase of the Quasi-Biennial Oscillation (QBO) exceeded the same yield for the eastward QBO. They attributed the difference to different rainfall patterns and drought frequency over this region for opposing phases of the QBO.…”
Section: Introductionmentioning
confidence: 99%
“…In the southern part of the East European plain, Cherenkova et al [43] demonstrated the average yield for winter wheat, spring wheat, and spring barley in the westerly phase of the Quasi-Biennial Oscillation (QBO) exceeded the same yield for the eastward QBO. They attributed the difference to different rainfall patterns and drought frequency over this region for opposing phases of the QBO.…”
Section: Introductionmentioning
confidence: 99%
“…However, [12] found the trend in drought over central and eastern Europe has been steady since the mid-20th century. In the southern East European plain, Cherenkova et al [13] demonstrated the average yield for winter wheat, spring wheat and spring barley in the westerly Quasibiennial Oscillation (QBO) phase exceeded the same yield for the eastward QBO. The 2010 drought in eastern Europe and Russia has been attributed to summer blocking episodes (e.g., [14) This work [14] associated five well-known dry and wet years with ENSO variability across the region.…”
Section: Introductionmentioning
confidence: 99%
“…Підписання Рамкової Конвенції ООН про зміну клімату представниками 175 країн свідчить про те, що зміна клімату є значною загрозою навколишньому середовищу та економічному розвитку. Дослідженню змін клімату присвячено велику кількість робіт науковців, однак локальні тенденції можуть відрізнятися від глобальних [1][2][3][4]. Аналіз попередніх досліджень дозволяє констатувати недостатню вивченість багаторічних змін клімату та його наслідків для Івано-Франківської області [4][5][6].…”
unclassified
“…Так, середні температури липня для Подільської і Передкарпатської частин області становлять 18-18,5°С, а в масиві Чорногора, на висоті понад 1800 м, -від 9 до 11°С. Тобто на кожні 100 м висоти температура знижується в середньому на 0,7°С [2]. У січні менша відмінність між середньомісячними температурами у горах і на рівнинах, відповідно 7-7,6°С і 4,5-5,0°С нижче від нуля [3].…”
unclassified
See 1 more Smart Citation